Akses pangan sebagai determinan utama konsumsi makanan energy-dense nutrient-poor (EDNP) pada remaja putri - Neysa Vania Camilla Purba; Fillah Fithra Dieny; Hartanti Sandi Wijayanti; Aryu Candra; A. Fahmy Arif Tsani (Jurnal Gizi Klinik Indonesia, 2026)
Food access is the main determinant of energy-dense nutrient-poor (EDNP) food consumption in adolescent girlsBackground: Energy-dense, nutrient-poor (EDNP) foods are a group of unhealthy foods that are popular among teenagers and are a causal factor in obesity. The amount of EDNP food consumed can be influenced by various factors.Objective: This study aimed to analyze the factors associated with EDNP food consumption in female adolescents at Cahaya Senior High School in Medan. Methods: The research design was cross-sectional, with 85 female students aged 15–18 years selected through simple random sampling. The data collected included subject characteristics; the percentage of EDNP food energy intake; the effects of social media exposure; the frequency and duration of exposure to food and beverage content; access to EDNP food; knowledge of nutrition; peer influence; and pocket money. Data analysis used the Kolmogorov-Smirnov normality test and the Spearman correlation test.Results: Effects of social media exposure (p=0.683), peer influence (p=0.188), allocation of pocket money for consumption (p=0.070), and knowledge of nutrition (p=0.267) were not related to the total frequency of EDNP food consumption. EDNP food access is related to the total frequency of EDNP food consumption. Access to food EDNP buying at food stalls, shops, restaurants, and takeaways had a strong correlation (r=0.778). Conclusions: Access to EDNP food was related to the total frequency of EDNP food consumption.